Neutral-point-clamped multilevel inverter development for total harmonic distortion (THD) reduction - Tuan Othman, Sharifah Sakinah (2014)
Over the last few decades, the Multilevel Inverter (MI) has attracted the attention of many researchers involved in this area of study. The MI is a new generation of DC-AC inverter that offers many advantages due to its features as compared to the conventional inverter as it is more suitable for handling large motor and high power applications. Mainly, it offers dv/dt stress reduction on switching devices due to its small voltage increment steps. Various methods have been used to determine the switching angle while constructing this circuit. Another favourable feature of this device is that it allows the Multilevel Inverter to operate at high voltages with low Total Harmonics Distortion (THD) without the use of a transformer. In this work, a three phase five-level Neutral-Point-Clamped Multilevel Inverter (NPCMI) has been investigated with the focus on determining its switching angle by using a proposed new Graphical Method Analysis (GMA) in order to obtain a lower THD output voltage percentage. The triggering angle and duration of the switching devices were determined and tested in order to achieve the finest sinusoidal-like output voltage waveform. The simulation model of a three phase NPCMI was modelled and the triggering sequences were tested to validate the performance of the MI. A simulation model of the three phase NPCMI was designed and developed using the Matlab/Simulink software package to analyse the performance. The THD of the output voltages with a variable switching frequency were measured and compared with the previous three-level NPCMI and other types of MI. In conclusion, a new technique to predict the improved switching angle of the three phase NPCMI is introduced to obtain a reduced THD output voltage waveform. The simulation has been verified by using a mathematical equation representation and also by comparison with the works of other researchers. From this work, a three phase fivelevel NPCMI that possesses a lower THD output voltage waveform has been successfully developed.